Analisis Pengaruh Motivasi, Lingkungan Kerja, Gaya Kepemimpinan, dan Disiplin terhadap Produktivitas Kerja pada Karyawan Perbankan Swasta di Kota Batam - Sentoso, Antony; Yuswardi, Yuswardi; Charmaine, Charmaine (REVITALISASI : Jurnal Ilmu Manajemen, 2023)
In the current era of globalization, HR management has become the main focus in achieving success for a company. Quality human resources will provide significant benefits and help companies gain competitive advantage amidst increasingly fierce business competition. This can be seen from HR’s ability to achieve company goals optimally through effective HR management practices. This research was conducted to examine the influence of motivation, work environment, leadership style, and discipline on work productivity. This research uses a quantitive method using a google form containing questions that are distributed to respondent. The total sample in this study was 342 respondent, the data was processed using SPSS version 26. The research result showed that the variables motivation, leadership style, and discipline had a significant effect on work productivity while the work environment had no significant effect.